PENGARUH EARNING PER SHARE, NET CASH FLOW DAN DEBT EQUITY RATIO TERHADAP RETURN SAHAM - Rokhman, M Taufik Noor (Manajemen & Bisnis Jurnal, 2016)
Abstract. This research is motivated by the automotive sector memengang important role in the Indonesian economy. The automotive sector has been used as one of the excellent industry by the Ministry of Industry. This study analyzes the effect of the simultaneous, partial Earning Per Share, Net Cash Flow and Debt Equity Ratio Return Against Automotive Company shares are listing on the Stock Exchange. This study places the automotive company listed on the Stock Exchange, in the period 2011-2014. The results showed simultaneous Earning Per Shae, Net Cash Flow and Debt Equity Ratio has an effect on stock returns automotive company listed on the Indonesia Stock Exchange. While partially Earning per share, Net Cash Flow has an effect on stock returns automotive company listed on the Indonesia Stock Exchange. Variable Debt Equity Ratio has no effect on stock returns automotive company listed on the Indonesia Stock Exchange. Automotive companies listed on the Indonesia Stock Exchange should increase stock returns so as to foster public confidence of investors in the company. As one of the efforts that need to be done is to show a good performance by generating Earning Per Shae and Net Cash Flow high as it can have a significant effect on stock returns. Keywords: Earning Per Share, Net Cash Flow, Debt Equity Ratio And Stock Return